African American Vernacular English in Dumbo (1941) Film: Bahasa Inggris Vernakular Afrika-Amerika Dalam Film Dumbo (1941) - Nabiilah, Syarafina; Alamsyah, Alamsyah (Jurnal Riseta Soshum, 2025)
This study aims to explore the popular English dialect which originated from the black people known as AAVE (African American Vernacular English), where its usage is not limited to the origin community only. Two focuses of this study will be on analysing the grammatical characteristics of AAVE and its underlying factors within the utterances from the three characters in Dumbo film, which are Timothy the mouse, the crow, and the clown by using qualitative method and the theory on AAVE dialect by Walt Wolfram and Rickford. This study applied the qualitative method and the data was gathered from coding character’s utterances. The results showed that the three characters used AAVE grammar, such as verb phrase, negation, and nominals. AAVE grammatical characteristics that were used by the characters are copula absence, completive done, sequential be done, other verbal phrase characteristics, ain’t, multiple negation, objective form them, and second person pronoun y’all. They also showed three factors on the AAVE grammar usage which are social class, age, and linguistic environment. These grammatical features are affected by the character’s class in the society as lower-worker group, character’s age which is in their adolescence, and the linguistic environment surrounding the character which depends on the level of familiarity felt by the characters regarding the topic or the person. The AAVE grammar alongside the factors found in the utterances of the three characters proved that they all represent the African American heritage which is the AAVE dialect despite having different races. The underlying factors influencing their utterances showed that a language will not be exempt from the various variables within the society.